Studi Home Range Penggunaan Taman Kota Studi Kasus Lapangan Puputan Margarana Niti Mandala, Denpasar, Bali - MANI, NI PUTU ARI CANDRA; ADNYANA, GEDE MENAKA; KOHDRATA, NANIEK (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol. 1, No. 2, Oktober 2012, 2012)
ABSTRACT A Study of Visitors Home Range for the Use of a City Park Case Study of Puputan Margarana Niti Mandala Square , Denpasar, Bali Puputan Margarana Niti Mandala Square in Denpasar, also commonly known as Renon Square, is one of the green open spaces in the city of Denpasar. People frequently visit the city park for doing outdoor activities. There are two objectives of this study. First, is to determine the service distance of Renon Square as a city park by its users in the context of the users’ home range. Second, is to find the users visit frequency at Renon Square. The research methods used in this study are observation and questionnaire method . The study shows that the area serves most by Renon Square as a city park is within the radius of 10 km. People live in Denpasar are the dominant user of the city park . The highest frequency of visit to Renon Square is one to two times a week . Keyword: home range, city park.
Keywords: home range; city park.